2018
DOI: 10.1080/14999013.2018.1468366
|View full text |Cite
|
Sign up to set email alerts
|

Gang membership, Mental Illness, and Negative Emotionality: A Systematic Review of the Literature

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 81 publications
(83 reference statements)
0
5
0
Order By: Relevance
“…Internal capacity refers to the internal skills (cognitive, psychological and behavioral) of an individual that may affect achievement of primary goods. A number of internal capacity issues related to street gang membership have been identified that can make attainment of the primary goods challenging, including: low Trait Emotional Intelligence, empathy and Theory of Mind, and high mental illness, impulsivity, callous-unemotional traits and endorsement of moral disengagement strategies (e.g., Mallion & Wood, 2018a;Osman & Wood, 2018). For instance, individuals with low empathy are less able to fulfil the primary good of Relatedness in a prosocial manner, increasing the risk of engaging with antisocial peer groups, such as street gangs (Wu & Pyrooz, 2015).…”
Section: Good Lives Model and Street Gang Members 15mentioning
confidence: 99%
See 1 more Smart Citation
“…Internal capacity refers to the internal skills (cognitive, psychological and behavioral) of an individual that may affect achievement of primary goods. A number of internal capacity issues related to street gang membership have been identified that can make attainment of the primary goods challenging, including: low Trait Emotional Intelligence, empathy and Theory of Mind, and high mental illness, impulsivity, callous-unemotional traits and endorsement of moral disengagement strategies (e.g., Mallion & Wood, 2018a;Osman & Wood, 2018). For instance, individuals with low empathy are less able to fulfil the primary good of Relatedness in a prosocial manner, increasing the risk of engaging with antisocial peer groups, such as street gangs (Wu & Pyrooz, 2015).…”
Section: Good Lives Model and Street Gang Members 15mentioning
confidence: 99%
“…This will require multidisciplinary input from various support systems (e.g., schools, family, social services, youth clubs and police) that are best placed to identify a child or young person's internal and external obstacles. Prevention strategies to overcome internal obstacles could include interventions aimed at improving emotion-and cognition-based skills (e.g., trait emotional intelligence, empathy, moral disengagement interventions; Aly, Taylor, & Karnovsky, 2014;Nelis, Quoidbach, Mikolajczak, & Hansenne, 2009) and rapid treatment for mental health issues (Osman & Wood, 2018). These could be implemented as universal classroom-based interventions or targeted interventions for those at most risk of street gang involvement (see Asmussen, Waddell, Molloy, & Chowdry, 2017, for an example of social and emotional learning interventions implemented in schools).…”
Section: Good Lives Model and Street Gang Members 29mentioning
confidence: 99%
“…For example, posttraumatic stress symptoms (e.g., Liberia: Johnson et al, 2008; DRC: Köbach, Schaal, & Elbert, 2015; Uganda: Neuner et al, 2012; U.K./U.S. : Osman & Wood, 2018; Australia: Zheng et al, 2016) and heightened levels of aggression (e.g., U.S.: Biddle et al, 2002; DR Congo: Köbach, Schaal, & Elbert, 2015; Burundi: Nandi et al, 2017; Colombia: Weierstall et al, 2013; Germany: Weierstall, Huth, et al, 2012; U.S.: Wilk et al, 2015), substance use disorders (Odenwald et al, 2009; Zheng et al, 2016), depression (Johnson et al, 2008; Osman & Wood, 2018), and suicidal ideation (Petering, 2016; Pompili et al, 2013) were reported. These psychological changes lead to increased violence in families and communities (e.g., Nandi et al, 2017; Reichenheim et al, 2011; Sparrow et al, 2017), affecting societies at large.…”
mentioning
confidence: 99%
“…It is important to note that the specific foci of these studies have differed and some of the findings across these studies have been mixed. However, this is most likely due to differences in methodologies, samples, and the early stages of this kind of research (for a discussion see Frisby- Wood, 2018). Generally, recent work has suggested that gang membership may be associated with numerous negative mental health outcomes including depression, anxiety, post-traumatic stress, perpetration trauma, hostility, paranoid ideation, psychosis, fear of victimisation, antisocial personality disorder, self-harm, suicide attempts and completions, pathological gambling, and substance dependence (Baćak et al, 2021;Coid et al, 2013;Connolly & Jackson, 2019;Frisby-Osman & Wood, 2020;Gaston et al, 2021;Kerig et al, 2016;Watkins & Melde 2016;.…”
Section: Individual/life-course Harmsmentioning
confidence: 99%
“…If this is the case for the most studied relationships in gang research (i.e., between gangs and violence/crime), this should also present cause for concern for less considered yet highly important relationships in the field. For example, the relationship between gang membership and mental health outcomes (Baćak et al, 2021;Osman & Wood, 2018), or between gang intervention programmes and possible adverse outcomes that extend beyond programme effectiveness (Barnett & Howard, 2018;McCord, 2003;Roman, 2021;Rubenson et al, 2020;Welsh & Rocque, 2014). As such, not only are theoretical understandings of gang-related phenomena left wanting, but it is unclear that our current approaches to pursuing explanations of such phenomena are suitable to address this need.…”
Section: Answering Causal Questions In Gang Research: the Criteria Of...mentioning
confidence: 99%